Self-healing films based on chitosan containing citric acid/choline chloride deep eutectic solvent. (May 2021) - Smirnov, Michael A.; Nikolaeva, Alexandra L.; Bobrova, Natalia V.; Vorobiov, Vitaly K.; Smirnov, Alexander V.; Lahderanta, Erkki; Sokolova, Maria P.
Abstract: Plasticized chitosan films with high content (67–82 wt%) of natural deep eutectic solvent (NADES) based on citric acid and choline chloride were prepared by solution casting method. The thickness of films was 19 ± 3 μm. The self-healing and water vapor bending movement of prepared films were demonstrated. Maximal mechanical characteristics of 84% elongation at break and 18 MPa strength, were achieved for a film containing 67 wt% of NADES. The formation of hydrogen bond network in the chitosan film due to replacement of citric acid with NADES (citric acid/choline chloride) was observed with FTIR. It is proposed that this network is responsible for self-healing ability of the chitosan–citric acid–choline chloride films. Structure, morphology and thermal properties of the prepared films are also discussed. Highlights: Chitosan (CS) was plasticized with citric acid/choline chloride (NADES). Maximal elasticity for film with 67 wt% of NADES was found. Self-healing ability of fully bio-based elastic CS/NADES film was demonstrated. CS/NADES film shows fast and reversible water vapor-induced movement. High NADES content (75 and 82 wt%) leads to inhomogeneity of films' structure.